Juggling academics in the absence of university policies to promote work-life balance: A comparative study of academic work and family in Chile and Spain - Montes-López, Estrella; Simbürger, Elisabeth (Education Policy Analysis Archives, 2021)
This article analyses the relationship between academic work and family life based on two studies on academic careers and gender carried out in Chile and Spain. Thirty-six semi-structured interviews were conducted with female university professors. The interviews address academic practice and working conditions and factors that hinder or facilitate the reconciliation of academic work and family life, such as the presence or absence of gender policies in universities. The research results show that it is the female academic as an individual who is in charge of reconciling work and life; that there is a strong gender bias in which men hardly appear as co-responsible; and that the university does not take up its institutional role of creating gender policies that create an environment that facilitates work-life balance.